2015
DOI: 10.1142/s0219525915500034
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Dynamics in Opinion Formation Model With Coupling of Social Communities

Abstract: By incorporating multi-community attachments into the continuous opinion formation model, we investigate the driving force for reaching consensus in networked systems. A phase transition from fragmentation to consensus is determined by the multiplex network structures and the coupling of different communities. A moderate number of layers and weak coupling are beneficial for consensus. The evolutionary dynamics in the present model is governed by the prolonged evolutionary time, which results from the dispariti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Such networks are conventionally called as interdependent systems, which fall in a different category of ours (see [25] for more backgrounds). Another work similar in spirit is [43], where the effect of multiple communities on opinion formation is investigated. It is shown that increasing the multiple layers is similar to promoting coupling between different communities.…”
Section: Introductionmentioning
confidence: 99%
“…Such networks are conventionally called as interdependent systems, which fall in a different category of ours (see [25] for more backgrounds). Another work similar in spirit is [43], where the effect of multiple communities on opinion formation is investigated. It is shown that increasing the multiple layers is similar to promoting coupling between different communities.…”
Section: Introductionmentioning
confidence: 99%
“…Each individual has a preference for the group-size n [50,51,52,53]. At each time step, firstly, we randomly choose an individual i with the preferred group-size n i from the total N individuals.…”
Section: The Modelmentioning
confidence: 99%
“…In the study of opinion dynamics, the binary-choice voter model and the Hegselmann-Krause model represent two distinctive kinds of opinion formation processes [23,24,25,26,27,28]. In the voter model, an individual's opinion has two possible states, labelled +1 and −1 respectively.…”
Section: Introductionmentioning
confidence: 99%